The Extraction of arsenic from tailing using naoh and NaHS - Lee, K.; Park, H.; Wang, J.; Yoo, Kyoungkeun (Taylor & Francis, 2011)
An arsenic leaching test was performed to extract arsenic contaminant from tailing sediment under basic condition with NaHS. The effects of particle size, NaHS concentration, temperature, and agitation speed were investigated to determine optimum leaching condition for the removal of arsenic from the tailing sediment. The leaching rate increases with decreasing the particle sizes of enargite and tailing sediment, which would result from the fact that arsenic distributes uniformly in the enargite and tailing sediment particle. The addition of NaHS accelerated the arsenic leaching rate, and this result suggests that some of arsenic in the tailing would exist as enargite or be bound to enargite. The arsenic leaching rates increased with increasing temperature and agitation speed. The arsenic leaching rates of enargite and tailing sediment were found to be 87% and 63%, respectively, under the conditions; particle size, -75 µm; temperature, 80°C; NaHS concentration, 1.5 kmol m -3 ; NaOH concentration, 1.1 kmol m -3 ; agitation speed, 400 rpm; pulp density, 5 kg m -3 (enargite) and 25 kg m -3 (tailing sediment). © 2011 Taylor & Francis Group, LLC.